The water agreement of 1927 and singapore's supremacy: the origins and implication for water supply between johor and singapore in the colonial period - A Rahman Tang Abdullah (Fakulti Kemanusiaan, Seni dan Warisan, UMS, 2014)
This article discusses the significance of the water agreement of 1927 in reference to the origins and historical development of water supply between Johore and Singapore during the colonial period. From historical perspective, this agreement is the first water agreement signed between Johore as a British protectorate and Singapore as the capital of the British Colony of The Straits Settlements. Despite the fact that this agreement had been abrogated in 1961 with the signing of the subsequent water agreements, most of its fundamental provisions still remains in effect. Thus, this article reveals the preceding events leading to the signing of the agreement, analyses the water agreements of 1927 and its implication for historical development of water supply to Singapore during the period from 1930’s to the 1950’s. It demonstrates that the issue of water supply between the two entities has tended to be in favour of Singapore because of Singapore’s political economic supremacy derived from her status of being the British Imperial, in South East Asia and from being the bearer of capital expenditure in the water construction in Johore. Consequently, Singapore was able to continuously exploit the water deal as one of those economic means to preserving her advantage.